2008
DOI: 10.1038/ajh.2008.188
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of G-protein  3 Subunit and Nitric Oxide Synthase Gene Polymorphisms on Carotid Artery Intima-media Thickness in Young Adults: The Bogalusa Heart Study

Abstract: These results indicate that the genetic variations of the eNOS gene in combination with the GNB3 gene jointly influence carotid artery wall thickening process in young adults, especially in blacks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…43 In summary, the 825T homozygosis of the GNB3 gene is significantly and independently associated with increased risk of incident CE in general population. Carrying the TT genotype exposes to additional risk of CE independent of blood pressure values and other established risk factors of stroke.…”
Section: Discussionmentioning
confidence: 99%
“…43 In summary, the 825T homozygosis of the GNB3 gene is significantly and independently associated with increased risk of incident CE in general population. Carrying the TT genotype exposes to additional risk of CE independent of blood pressure values and other established risk factors of stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Reports showing an association between the G894T polymorphism, vascular complications and hypertension in humans are not consistent [ 10 17 , 36 ]. The meta-analysis of Niu and Qi indicated that the T894 allele may be associated with an increased risk of hypertension.…”
Section: Discussionmentioning
confidence: 99%